Corrosion assessment of infrastructure assets in coastal seas. Issue 3 (1st September 2016) - Valdez, Benjamín; Ramirez, Jorge; Eliezer, Amir; Schorr, Michael; Ramos, Rogelio; Salinas, Ricardo
ABSTRACT: The seas play an essential role for the peoples living on their coastal regions, since the marine infrastructure is located in the coasts. Seawater is a corrosive environment that affects infrastructure particularly in polluted seawater. Corrosion and pollution are pernicious chemical, physical processes that impair the quality of the environment and the durability of the marine structures and materials. They are aggravated by the discharge into the sea coast of municipal, industrial and agricultural effluents, which contain and produce toxic and highly corrosive components by biological and chemical degradation. Reinforced concrete and carbon steel are the main engineering materials used for the construction of marine installations and equipment but other metals and alloys: aluminium; copper, stainless steels are applied, too. Laboratory and field corrosion tests in seawater were carried out applying gravimetric, electrochemical and surface examination methods, based on American Society of Testing and Materials (ASTM) and National Association of Corrosion Engineers (NACE) standards. This work is the result of a cooperation between academic institutions in Mexico and Israel. The data generated advance the management of sea corrosion prevention and mitigation, and provide a guide for marine infrastructure maintenance and corrosion control. Several cases of corrosion in the sea coasts based on the authors experience and knowledge are presented.